2021
DOI: 10.1093/cz/zoab044
|View full text |Cite
|
Sign up to set email alerts
|

Female preferences for male golden snub-nosed monkeys vary with male age and social context

Abstract: Age is a key factor affecting sexual selection, as many physical and social traits are age-related. Although studies of primate mate choice often consider particular age-related traits, few consider the collective effects of male age. We tested the hypothesis that female golden snub-nosed monkeys Rhinopithecus roxellana prefer prime aged males (10–15 years) over younger and older males. We examined a habituated, provisioned troop during a 3-year study in the Qinling Mountains, China. Prime age males were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…We found that male age significantly explains variation in both the formation and duration of male–female social pairings, and the number of females with which OMU leader males paired during the study period, with Old and Prime males having an advantage over Adult males (Tables 3 and 4). This concurs with another recent study showing that males of Prime age (10–15 years old) were more likely to achieve OMU leader male status and pair with more females than younger and older males (Yang et al, 2021). OMU leader males have an advantage over bachelor males for mating opportunities (Guo et al, 2010) so female preferences have the potential to result in increased mating success for Prime males (Clutton‐Brock & Isvaran, 2007; McCleery et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…We found that male age significantly explains variation in both the formation and duration of male–female social pairings, and the number of females with which OMU leader males paired during the study period, with Old and Prime males having an advantage over Adult males (Tables 3 and 4). This concurs with another recent study showing that males of Prime age (10–15 years old) were more likely to achieve OMU leader male status and pair with more females than younger and older males (Yang et al, 2021). OMU leader males have an advantage over bachelor males for mating opportunities (Guo et al, 2010) so female preferences have the potential to result in increased mating success for Prime males (Clutton‐Brock & Isvaran, 2007; McCleery et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Evolution would favor mechanisms that prevent females from jeopardizing social relations within units. In our study population, social cohesion and unit size are associated with the dominance hierarchy among units in the breeding band (Fang et al 2018(Fang et al , 2022Yang et al 2021). In addition, high-ranking units often lead group movements and have the priority of accessing food resources (Wang et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…First, we suspect that females can strategically use the breeding status of other females to guide their migration decisions to avoid intrasexual competition. At least in our study population, females have strong control over mate choice and the timing of copulation; they are virtually free to migrate to other OMUs or start a new unit without the threat of male coercion, but they also have a strong in uence in the reign of current residential males (Fang et al 2018(Fang et al , 2022Qi et al 2020;Yang et al 2021). In addition, living in a multi-level society confers knowledge about other OMUs, due to continuous and close inter-unit associations (forming a breeding band).…”
Section: Discussionmentioning
confidence: 96%